CYFIP2: potential pancreatic cancer biomarker and immunotherapeutic target - Cong Xiao; Xiaojuan Zhang; Bobo Hou; Ping Wan; Zhenjun Cao; Xuefeng Rao (Discover Oncology)
Abstract Objective It has been shown that the CYFIP2 (Cytoplasmic FMR1-interacting protein 2) gene is apoptosis p53-dependent and is associated with poor prognosis in malignant tumors such as gastric cancer and other and cervical cancer. However, the prognostic potential of CYFIP2 in pancreatic cancer remains unclear. In this work, we first explain the great potential of CYFIP2 malignant progression from a broader perspective (pan-cancer) and confirm its oncogenic value in pancreatic cancer. Methods The Cancer Genome Atlas (TCGA), Genotype-Tissue Expression (GTEx) database, CELL and GEO databases were utilized to explore the distribution of the CYFIP2 gene in human cancers. Data were analyzed using a variety of web-based platforms and software such as R (4.3.2), UCSC, MethSurv, Cytoscape (v3.10.2), UALAND, STRING, TISIDB, Harmonizome 3.0, TIMER 2.0, TCIA and TIDE. The R packages R packages “limma” and “ggplot2” were used to compare and visualize CYFIP2 mRNA expression. The R packages “survminer” and “survival” were used to statistically analyze the relationship between CYFIP2 expression and the survival and prognosis of tumor patients. the R package “ss GSEA” was used to assess the correlation between CYFIP2 expression and immune infiltration. Gene Ontology (GO), Kyoto Encyclopedia of Genes and Genomes (KEGG) and Gene Set Variation Analysis (GSVA) were used to explore the multiple biological functions and regulatory pathways in which CYFIP2 co-expressed genes co-engage in pancreatic cancer. The R package “maftool” was used to explore somatic mutation information in pancreatic cancer, and the TIDE database and the R package “oncoPredic” were used to explore immunotherapeutic responses and sensitive drugs. Pancreatic cancer cell lines were constructed with the specific expression of CYFIP2 mRNA, and their invasive and metastatic abilities were analysed using scratch and transwell assays. Results Bioinformatics analysis and in vitro experiments confirmed that CYFIP2 was differentially expressed in a variety of tumors and correlated with clinical stage, and could be used as a potential marker for evaluating the prognosis and immunotherapy of a variety of tumors, including KIRC (Kidney renal clear cell carcinoma), PAAD (Pancreatic adenocarcinoma), PAAD (Pancreatic adenocarcinoma), SKCM (Skin Cutaneous Melanoma), and UCEC (Uterine Corpus Endometrial Carcinoma).Mutations in the CYFIP2 gene and methylation indices can affect the prognosis of tumor patients. In addition, we found that CYFIP2 expression values in pancreatic cancer were positively correlated with the expression of most immune cells, especially CD8 + T Cells, and significantly negatively correlated with macrophages M0, and negatively correlated with the metastatic and invasive ability of pancreatic cancer cells, which may provide new strategies and ideas for pancreatic cancer immunotherapy.